Making academic OER easy: Reflections on technology and openness at Oxford University - Melissa H. Highton; Jill W. Fresen; Joanna Wild (Flexible Learning Association of New Zealand, 2011)
Due to its stringent entry requirements, academic reputation and world ranking, Oxford University in the United Kingdom is perceived by some as being a closed, exclusive, and elitist institution. As learning technologists working in the institution, we have experienced an enthusiasm amongst academic colleagues for openness in publication and practice enhanced by new technologies, which reflects their long-demonstrated commitment to publication and the dissemination of new knowledge. Advances in digital technologies and the emergence of online platforms for global dissemination have enabled Oxford University seminars, lectures, and public addresses, many by famous figures, to be shared with an international audience. This article charts the journey Oxford has made in opening up educational content and describes the ways in which we have worked to ensure that the value added by technology aligns with current academic practice in the institution.